A Case of Urinary Incontinence Patients After Having an Vertebrae Lumbales Operation - Lim Se-young; Kim Sung-wook; Kim Tae-hui; Jung Sung-yub; Cho Yoon-chul; Kim Chul-soo (Korean Pharmacopuncture Institute, 2003)
Objective : The purpose of this study is to show that there was a significant result in prescribing Herb remedy and Korean-Bee-Venom acupuncture and acupuncture & moxibustion therapy to Urinary incontinence patients due to Neurologic Bladder caused by Cauda equina syndrome after having an vertebrae lumbale operation. Methods : The methods used in this study was observe the patient's subjective improvement, valuation of the bladder function and the change of the sensibility drop when Herb remedy and Korean-Bee-Venom acupuncture and acupuncture was applied . Results : When acupuncture and Korean-Bee-Venom acupuncture was both applied the function of Bladder changed from score 10 to 0 and the Grade of Urinary Incontinence changed from Grade III to 0 also with the sensibility drop. Conclusion : The results show that when using Umnungchon(SP9), Yangnungchon (GB34), Taedon(LR1), Kokkol(CV2) there was an effect to some degree to the Urinary incontinence patients but when Korean-Bee-Venom was acupunctured to Kwanwon(CV4) and Kihae(CV6) the effect increased. Further studies and examples for evidence are required.